Assuring the Adversary System - Griffin Bell (Washington University Law Quarterly, 1983)
How have the lawyers of America in the intervening century-and-ahalf honored the trust which they assumed? For it is a trust. We have no perpetual franchise to practice law as it is now practiced. We have a monopoly but it is not guaranteed. The courts are jammed; there are great delays in obtaining justice. Justice is expensive, and there is little finality in criminal law. This lecture reflects on the most pervasive issues in the legal world and suggests the changes needed to accommodate the system of law.
Keywords: Justice administration; Adversary system; United States